Christine de Pizan's changing opinion : a quest for certainty in the midst of chaos - Kelly, Douglas (Gallica (Woodbridge (Suffolk, England)), 2007)
'Christine de Pizan's Changing Opinion' examines the evolution of Christine's thought on true and false opinion. She reflected deeply on the subject of opinion while analysing, evaluating, challenging, and changing her own and others' opinions in her lifelong quest for certain truth.